ARTIFICIAL HEART VALVES: INDICATIONS FOR IMPLANTATION, THEIR FUNCTION, AND MODERN TECHNOLOGIES - Do’lanova Maftunaxon Shavkatbek qizi; Erkaboyeva Mohirabonu Ulug’bek qizi (Innovate Conferences, 2025)
This scientific article provides an analytical overview of the functional structure of heart valves, their significance, and defects caused by diseases. The primary function of heart valves is to ensure unidirectional blood flow between the heart chambers and blood vessels. When valves are damaged, serious problems occur in the cardiovascular system, which can be life-threatening. The article analyzes mechanical and biological artificial valves that replace native valves, discussing their structure, advantages, and disadvantages. It especially covers clinical recommendations on choosing the valve type based on the patient’s age, overall heart condition, and other individual factors. Mechanical valves offer long durability but require lifelong anticoagulation therapy; biological valves have shorter lifespan but are closer to natural valves. The article also discusses modern technologies such as TAVI (Transcatheter Aortic Valve Implantation), 3D-printed valves, and hybrid technologies. These methods offer less risk compared to traditional invasive (open-heart) surgeries and reduce recovery time. This work is useful theoretically and practically for students studying cardiac surgery and cardiology, practicing physicians, and specialists working with medical technologies.
Keywords: Artificial heart valves, heart valve defects, mechanical valve, biological valve, TAVI technology, valve prosthesis, cardiac surgery, circulatory disorders, cardiology, anticoagulants, 3D-printed valves, mitral and aortic valves, modern medical technologies, valve replacement surgery, minimally invasive surgery.